2019
DOI: 10.1080/09297049.2019.1648641
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal socioeconomic status and social support are associated with neonatal brain morphology, toddler language and psychiatric symptoms

Abstract: Few studies have assessed the association of parental SES with brain measures in neonates, at a time when exposure to the postnatal environment is minimal. Social support may buffer the adverse consequences of SES, and has been associated with better cognitive -emotional development in children. We studied the association of prenatal SES and social support with neonatal brain structure, and toddler cognition and psychiatric symptoms. In a sample of 37 healthy neonates, we correlated a measure of SES and marita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 85 publications
1
52
0
Order By: Relevance
“…One possibility is that in some infants, higher FA values in the newborn period reflect more rapid neural development and premature myelination, which in turn makes them more susceptible to the current environment. This view is supported by studies linking neurotrophic factors to brain maturation and neuroplasticity in the postnatal period ( Dyer et al., 2016 ; Kowiański et al., 2018 ), as well as a growing number of studies reporting that early adversity is associated with both accelerated brain maturation and a risk for later developmental problems ( Callaghan and Tottenham, 2016 ; Posner et al., 2016 ; Thijssen et al., 2017 ; Spann et al., 2019 ). Further, in line with our findings, one adult study has shown that lower FA values may reflect prolonged/treatment-resistant depression (less plasticity and response to environment) ( De Diego-Adeliño et al., 2014 ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…One possibility is that in some infants, higher FA values in the newborn period reflect more rapid neural development and premature myelination, which in turn makes them more susceptible to the current environment. This view is supported by studies linking neurotrophic factors to brain maturation and neuroplasticity in the postnatal period ( Dyer et al., 2016 ; Kowiański et al., 2018 ), as well as a growing number of studies reporting that early adversity is associated with both accelerated brain maturation and a risk for later developmental problems ( Callaghan and Tottenham, 2016 ; Posner et al., 2016 ; Thijssen et al., 2017 ; Spann et al., 2019 ). Further, in line with our findings, one adult study has shown that lower FA values may reflect prolonged/treatment-resistant depression (less plasticity and response to environment) ( De Diego-Adeliño et al., 2014 ).…”
Section: Discussionmentioning
confidence: 93%
“…As mentioned earlier, a growing number of studies have linked early life adversities to accelerated brain maturation (e.g. Gee et al., 2013 ; Spann et al., 2019 ). Thus, poorer parental mental health prior to and during pregnancy may program child brain development through epigenetic mechanisms toward more accelerated neurodevelopment reflected in white matter microstructure.…”
Section: Discussionmentioning
confidence: 99%
“…Occupational scores range from 1 (e.g., service workers) through 9 (e.g., higher executives and major professionals), while educational scores range from 1 (e.g., lower than 7th-grade education) through 7 (e.g., graduate-level education). The Hollingshead Index continues to be among the most widely used, brief, valid, and reliable estimate of SES in health and imaging research (e.g., Bornstein et al, 2003 ; Lawson et al, 2013 , 2017 ; Cohen-Zimerman et al, 2019 ; Spann et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Such an association would indicate that preventative efforts should encompass the period before birth and would also elucidate the developmental neurobiology underlying mental illness more generally. One recent study has linked prenatal SES with neonatal cortical volumes; ( Spann et al, 2020 ) however, whether neonatal resting state functional connectivity varies with SES remains unknown. To address this issue, we longitudinally examined associations between socioeconomic status at birth, brain connectivity at birth, and psychiatric symptoms at age 2 years.…”
Section: Introductionmentioning
confidence: 99%